Degradation of C. I. Direct Red 80 by the Electro-Fenton Process - Borges, Boaventura; Baía, Ana; Lopes, Ana; Pacheco, Maria José; Ciríaco, Lurdes; Fernandes, Annabel (KnE Materials Science, 2022)
Electro-Fenton process was applied in the degradation of the textile dye C. I. Direct Red 80 (DR80), using a boron-doped diamond anode and a carbon-felt cathode. The influence of the applied current density and of the type of iron source was evaluated. The iron sources studied were iron sulfate, ferric chloride, iron oxide and chalcopyrite, a natural iron-containing mineral. The obtained results showed that the electro-Fenton process is effective in the DR80 degradation and in the pollutant load elimination. Higher treatment efficiencies were attained when using iron sulfate as iron source. Still, the results obtained with the natural mineral chalcopyrite were quite promising. Although DR80 removal was more efficient at lower applied current densities, the same was not observed for the chemical oxygen demand removal, indicating that, at lower applied current densities, the dye is not completely mineralized, but rather transformed into other by-products. Keywords: C. I. Direct Red 80; Advanced oxidation processes; Electro-Fenton, Borondoped diamond anode, Carbon-felt cathode.